ANALISIS KOMPARATIF PENGATURAN DAN PENERAPAN PIDANA PENJARA TERHADAP TINDAK PIDANA PEMBUNUHAN DALAM KUHP BARU INDONESIA DAN PENAL CODE TIMOR-LESTE - Domingos Pascoal Fernandes (Darma Cendika Catholic University, 2025)
This study examines the comparative regulation and application of imprisonment for the crime of murder under the Indonesian Criminal Code (Law No. 1 of 2023) and the Penal Code of Timor-Leste (Decree-Law No. 19/2009). The research aims to analyze the legal framework governing murder offenses to compare the implementation of imprisonment through the perspective of judicial decisions and sentencing policies in both countries. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The analysis is conducted through the examination of primary and secondary legal materials, including legislation and court decisions. And relevant scholarly literature. The findings reveal significant differences in the philosophical orientation of criminal punishment between the two legal systems. Indonesia maintains a broader spectrum of sanctions, including conditional death penalty provisions and long-term imprisonment, reflecting a combination of retributive and deterrent objectives. In contrast, Timor-Leste constitutionally prohibits the death penalty and emphasizes proportionality, human rights protection, rehabilitation, and social reintegration. The study further demonstrates that the effectiveness of imprisonment is not determined solely by the severity or duration of punishment but also by the consistency of legal application, sentencing guidelines, and the quality of correctional institutions. Indonesia faces challenges such as prison overcrowding, sentencing disparities, and limited rehabilitation programs, while Timor-Leste encounters constraints related to institutional capacity and correctional infrastructure. The comparative analysis indicates that both countries can learn from each other in developing a more balanced criminal justice system that harmonizes public protection, legal certainty, rehabilitation, and respect for human rights. Ultimately, effective imprisonment policies require a proportional approach that balances deterrence, rehabilitation, and the protection of fundamental rights within a modern rule of law framework.